Diagnóstico del proceso de cristalización del sulfato de cobre pentahidratado mediante revisión bibliográfica (2021)
The purpose of this project is to diagnose the crystallization process to obtain copper sulfate pentahydrate. Initially, we proceeded to make an approach to the product, taking into account its properties, characteristics, applications and how an increase in the market for copper sulfate pentahydrate has been evidenced since 2015 in Colombia. Following this, various bibliographic reviews were carried out (Science Direct, Google Scholar, Reaxys, etc.), in order to have a more in-depth knowledge about the crystallization process and also to know the factors that are involved in it, to finally analyze the variables involved in crystallization.